Critical Thinking Ability on Temperature and Heat in Learning with Problem Based Learning Models - Baiq Inayah Rahmaniah Puteri; Muh. Makhrus; Hikmawati (Prodi Fisika FKIP Unram, 2023)
This study aims to determine the effect of the problem-based learning model on students' critical thinking skills in the subject matter of temperature and heat. This type of research is quasi-experimental with a pretest-posttest control group design. The population of this study was all students in class XI MIPA at SMAN 2 Praya, while the sample was taken using a random sampling technique so that students in class XI MIPA 3 were selected as the experimental class and students in class XI MIPA 4 as the control class. The instrument used to measure students' critical thinking skills during learning activities is LKPD which is equipped with questions that refer to indicators of critical thinking skills, and the non-test instrument used is in the form of student response questionnaires to LKPD. The results of the analysis of the level of critical thinking skills of students during learning activities show a very critical category for students in the experimental class and a critical category for students in the control class. The results of the student response questionnaire analysis showed that the student response to the LKPD was 79% in the positive category. Keywords: Problem Based Learning, Critical Thinking Ability, Temperature, heat